An experimental study on tolerance to hypoxia in tardigrades - Hagelbäck, Philip; Jönsson, K. Ingemar (Frontiers in Physiology, 2023)
Tardigrades are small aquatic invertebrates with well documented tolerance to several environmental stresses, including desiccation, low temperature, and radiation, and an ability to survive long periods in a cryptobiotic state under arrested metabolism. Many tardigrade populations live in habitats where temporary exposure to hypoxia is expected, e.g., benthic layers or substrates that regularly undergo desiccation, but tolerance to hypoxia has so far not been thoroughly investigated in tardigrades. We studied the response to exposure for hypoxia (<1 ppm) during 1 to 24 hours in two tardigrade species, Richtersius cf. coronifer and Hypsibius exemplaris. The animals were exposed to hypoxia in their hydrated active state. Survival was high in both species after the shortest exposures to hypoxia but tended to decline with longer exposures, with almost complete mortality after 24h in hypoxia. Richtersius cf. coronifer tended to be more tolerant than Hypsibius exemplaris. When oxygen level was gradually reduced from 8 to 1 ppm, behavioral responses in terms of irregular body movements were first observed at 3-4 ppm. The study shows that both limno-terrestrial and freshwater tardigrades are able to survive exposure to severe hypoxia, but only under a relatively short period of time. It also indicates that tardigrade species have different sensitivity and response patterns to exposure to hypoxia. These results will hopefully encourage more studies on how tardigrades are affected by and respond to hypoxic conditions.